Interferon-γ: biological function and application for study of cellular immune response - A. A. Lutckii; A. A. Zhirkov; D. Yu. Lobzin; M. Rao; L. A. Alekseeva; M. Maeurer; Yu. V. Lobzin (Журнал инфектологии)
Cellular immune response plays a central role in control of intracellular pathogens like viruses, some bacteria and parasites. Evaluation of presence, specificity and strength of cellular immune response can be done by investigation of reaction of immune cells to specific stimulus, like antigen. The major cellular reactions to antigen stimulation are production of cytokines, proliferation and cytotoxicity. This review is focused on interferon-gamma as one of the central Th1 cytokines: its biology, immunological role and application as marker of cellular immune response.